Fiber-coupled quantum light sources based on solid-state quantum emitters. (1st December 2022) - Bremer, Lucas; Rodt, Sven; Reitzenstein, Stephan
Abstract: Photonic quantum technology is essentially based on the exchange of individual photons as information carriers. Therefore, the development of practical single-photon sources that emit single photons on-demand is a crucial contribution to advance this emerging technology and to promote its first real-world applications. In the last two decades, a large number of quantum light sources based on solid-state emitters have been developed on a laboratory scale. Corresponding structures today have almost ideal optical and quantum-optical properties. For practical applications, however, one crucial factor is usually missing, namely direct on-chip fiber coupling, which is essential, for example, for the direct integration of such quantum devices into fiber-based quantum networks. In fact, the development of fiber-coupled quantum light sources is still in its infancy, with very promising advances having been made in recent years. Against this background, this review article presents the current status of the development of fiber-coupled quantum light sources based on solid-state quantum emitters and discusses challenges, technological solutions and future prospects. Among other things, the numerical optimization of the fiber coupling efficiency, coupling methods, and important realizations of such quantum devices are presented and compared. Overall, this article provides an important overview of the state-of-the-art and the performance parameters of fiber-coupled quantum light sources that have been achieved so far. It is aimed equally at experts in the scientific field and at students and newcomers who want to get an overview of the current developments.